Dasatinib Outcomes Maintained Over 5 Years - Hitt Nichols, Emma (MD Conference Express, 2014)
A new analysis from the DASISION trial showed that long-term treatment with dasatinib, compared with imatinib, in patients with treatment-naïve, chronic phase myeloid leukemia improved rates of major molecular response and molecular response, but not overall survival or progression-free survival, in the patients who completed 5 years of follow-up, without new safety signals.